Green synthesis of xanthene and acridine-based heterocycles of pharmaceutical importance: a review - Burange, Anand S.; Gadam, Komal G.; Tugaonkar, Prajyot S.; Thakur, Seema D.; Soni, Ravish K.; Khan, Rubej R.; Tai, Mubashira S.; Gopinath, Chinnakonda S. (Environmental Chemistry Letters, 2021)
Xanthene and acridine-based heterocyclic compounds find applications in cancer chemotherapy, biological staining and laser dyes and are known for their antibacterial and anti-tumor properties. Here we review green catalytic routes for the synthesis of 1,8-dioxo-octahydroxanthenes, 1,8-dioxo-decahydroacridines and related heterocyclic molecules with catalysts such as metal oxides, mixed metal oxides, resins, supported organocatalysts, heteropolyacids, carbon-based materials, zeolites, sulfides and ionic liquids. We compare protocols for their catalytic activities, and proposed mechanisms are discussed.
Keywords: green chemistry; heterocycles; heterogeneous catalysis; Metal oxides; nanocatalysis